Reading Genesis ten methods - Hendel, Ronald S. (Cambridge ; New York : Cambridge University Press, 2010)
"Reading Genesis presents a panoramic view of the most vital ways that Genesis is approached in modern scholarship. Essays by ten eminent scholars cover the perspectives of literature, gender, memory, sources, theology, and the reception of Genesis in Judaism and Christianity. Each contribution addresses the history and rationale of the method, insightfully explores particular texts of Genesis, and deepens the interpretive gain of the method in question. These ways of reading Genesis, which include its classic past readings, map out a pluralistic model for understanding Genesis in - and for - the modern age"--Provided by publisher.
Machine generated contents note: Introduction Ronald Hendel; 1. Literature Robert Alter; 2. Cultural memory Ronald Hendel; 3. Sources and redaction Robert S. Kawashima; 4. Gender and sexuality Ronald Hendel, Chana Kronfeld, and Ilana Pardes; 5. Inner-biblical interpretation Yair Zakovitch; 6. Rabbinic interpretation Dina Stein; 7. Interpretation in the early church Richard A. Layton; 8. Translation Naomi Seidman; 9. Modern literature Ilana Pardes; 10. Modern theology John J. Collins.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Bible. -- Criticism, interpretation, etc; Bible -- Hermeneutics; Electronic books